Infective myositis, an uncommon presentation of melioidosis: a case report and review of the literature - Jayawardena, Nuwan (J Med Case Rep, 2019)
BACKGROUND: Melioidosis is considered endemic in certain areas of the world. Musculoskeletal and soft tissue involvement are relatively uncommon presentations in melioidosis. We present a case of infective myositis in a patient with melioidosis in Sri Lanka, which is not considered an endemic country. Even though multiple cases of melioidosis have been reported with an increasing number in Sri Lanka, infective myositis secondary to melioidosis was not reported previously. CASE PRESENTATION: A 60-year-old Sinhalese man with diabetes presented with fever of 4 months’ duration and a limp with a painful lump on the right side of the upper thigh of 2 months’ duration. He had been treated in a local hospital for community-acquired pneumonia 3 weeks prior to this admission, for which he had received intravenous meropenem and teicoplanin with intensive care unit admission. He had a 0.5-cm × 0.5-cm tender lump over the right vastus lateralis muscle, and contrast-enhanced computed tomography of the area showed an ill-defined, heterogeneously enhancing, hypodense area involving the vastus lateralis, vastus intermedius, and quadratus femoris, suggestive of infective myositis but without abscess formation. Histopathology of the muscle biopsied from the vastus lateralis showed suppurative inflammation of subcutaneous fat with connective tissue necrosis and muscle infiltrated by lymphocytes. These features are suggestive of infective myositis possibly due to melioidosis. Although the result of a culture taken from the muscle biopsy was negative, the patient’s antibody titer was strongly positive for melioidosis. He did not show any other areas with infected foci. He was treated with intravenous meropenem for 2 weeks and responded well. He was discharged with trimethoprim-sulfamethoxazole for 6 months as a maintenance therapy. CONCLUSION: Melioidosis is commonly an undiagnosed disease that has a wide variety of clinical presentations. Myositis in melioidosis is uncommon, and careful evaluation is mandatory to avoid misdiagnosis of this treatable but fatal disease. The clinician should have a high index of clinical suspicion, and further clinical and epidemiological studies are needed to determine the true burden of the disease.